Metal Content in Dandelion (Taraxacum officinale) Leaves: Influence of Vehicular Traffic and Safety upon Consumption as Food - Agnese Giacomino; Mery Malandrino; Maria Laura Colombo; Sergio Miaglia; Pietro Maimone; Sebastiano Blancato; Eleonora Conca; Ornella Abollino (Journal of Chemistry)
The widespread distribution of the common dandelion, that is, Taraxacum officinale, along with its ability to tolerate a wide range of environmental conditions, makes this plant a good candidate as biological monitor of environmental metal contamination. Taraxacum officinale leaves growing spontaneously in meadows and along the streets are traditionally picked up and eaten in Italy as salad, so it is important to know the concentrations of potentially toxic elements contained in them from the point of view of food safety. For these reasons the concentrations of Cd, Cr, Cu, Fe, Mn, Pb, and Zn were determined in dandelion leaf and underlying soil samples collected at 12 sites in the province of Cuneo (Piedmont, Italy) in the vicinity of streets or roundabouts. The concentrations were compared with reference values for plant and soils and with maximum allowable concentrations in edible vegetables. Neither dandelion nor soil samples were found to be polluted by metals, but the comparison with limits for vegetables suggests that caution should be used in consuming spontaneously growing vegetables.